Investigating Few Presumptions Regarding the Academic Performance of Students : A Study on MBA Scholars in Knowledge Park, Greater Noida - Mishra, Amitabh (Prabandhan: Indian Journal of Management, 2018)
Since a long time, researchers have been exploring various dimensions of studentsâ€™ academic performance, including- various factors influencing academic performance and the nature of relationship among them; methods of improvement; the impact of academic performance on the students’ career, country, community, etc. The study in hand investigated the report cards of 1645 newly admitted MBA students (enrolled in 29 different institutions of Knowledge Park, Greater Noida, Uttar Pradesh) and tested the authenticity of few popular presumptions about the academic performances of students in Indian society. The research used a descriptive research design and a judgmental sampling technique. The data-sets were cross tabulated and analyzed using the tools of descriptive statistics. The hypotheses were tested using two tailed t - tests (i.e. paired - samples t - test and independent - samples t - test) for large samples. Finally, the research provided statistical evidence to accept or reject the validity of few popular presumptions about Indian students. The research disapproved a popular presumption that ’the students who perform well in internal examinations will also perform well in external examinations.’ Further, the research provided a rationale to validate the presumption that ’the females are more studious and perform better than male students.’ Further, the research also approved another presumption that ’the origin of the studentsâ€™ religion does not indicate or hint at their academic performance.’